Level of emotional intelligence among a sample of kindergarten children in the city of Lattakia and its relationship with some variables - شريبه بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aimed to measure the level of emotional intelligence among a sample of kindergarten children in the city of Latakia and to reveal its relationship with gender and age variables among a sample of (94) children whose age ranged from 4-6 year in 2018-2019. The researcher have developed non-verbal scale of emotional intelligence composed of five dimensions: (1) Understanding of Emotions. (2) Empathy. (3) Self-Awareness. (4) Managing Emotion. (5) Social Skills. The researcher also used a descriptive approach and the results of the research indicated that the level of emotional intelligence for kindergarten children in the city of Latakia is medium. The results didn’t show statistically significant differences according to gender and age variables.